Determinants of Influenza Vaccine Uptake in Patients With Cardiovascular Disease and Strategies for Improvement - Priyanka Bhugra; Gowtham R. Grandhi; Reed Mszar; Priyanka Satish; Rahul Singh; Michael Blaha; Ron Blankstein; Salim S. Virani; Miguel Cainzos‐Achirica; Khurram Nasir (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Cardiovascular disease (CVD) is the leading cause of death and disability worldwide. Influenza infection is associated with an increased risk of cardiovascular events (myocardial infarction, stroke, and heart failure exacerbation) and mortality, and all‐cause mortality in patients with CVD. Infection with influenza leads to a systemic inflammatory and thrombogenic response in the host body, which further causes destabilization of atherosclerotic plaques. Influenza vaccination has been shown to be protective against cardiovascular and cerebrovascular events in several observational and prospective studies of at‐risk populations. Hence, many international guidelines recommend influenza vaccination for adults of all ages, especially for individuals with high‐risk conditions such as CVD. Despite these long‐standing recommendations, influenza vaccine uptake among US adults with CVD remains suboptimal. Specifically, vaccination uptake is strikingly low among patients aged <65 years, non‐Hispanic Black individuals, those without health insurance, and those with diminished access to healthcare services. Behavioral factors such as perceived vaccine efficacy, vaccine safety, and attitudes towards vaccination play an important role in vaccine acceptance at the individual and community levels. With the ongoing COVID‐19 pandemic, there is a potential threat of a concurrent epidemic with influenza. This would be devastating for vulnerable populations such as adults with CVD, further stressing the need for ensuring adequate influenza vaccination coverage. In this review, we describe a variety of strategies to improve the uptake of influenza vaccination in patients with CVD through improved understanding of key sociodemographic determinants and behaviors that are associated with vaccination, or the lack thereof. We further discuss the potential use of relevant strategies for COVID‐19 vaccine uptake among those with CVD.